THE EFFECT OF USING ENGLISH SONG IN TIKTOK VIDEO ON STUDENTS’ READING ABILITY OF 2021/2022 NINTH YEAR STUDENTS OF SMP SWASTA KARYA BAKTI SELESAI - ummi umara yusuf (STKIP Budidaya Binjai, 2022)
ABSTRACTThe objective of this study is to find out whether there was an effect of using English song in TikTok Video on students’ reading ability of 2021/2022 ninth year students of SMP Swasta Karya Bakti Selesai. The design in this study was quasi-experimental design by using post-test non-equivalent control group design. This study was conducted with ninth grade students of SMP Swasta Karya Bakti Selesai as the population of study. The sample was taken by using cluster random sampling, with 40 students as the sample of this study. The researcher used class IX-A which consist of 20 students as the experimental class and IX- B which consist of 20 students as the control class. The researcher used test as the instrument of collecting the data. The data collected from this study were analyzed using t-test formula. The results of this study that was a positive effect of the result students’ reading ability after using English song in TikTok video as media. It can be seen from the data analysis, it was found that value of t-observed (t0) was higher than t-table (tt). The result from calculating the data was t-observation (t0 = 3,48) and t-table (tt =1,686 ), it means, t0 is higher than tt in significant 5%, so the null hypothesis (H0) is rejected, and the alternative hypothesis (Ha) is accepted. In other words, using English Song in TikTok video had effect on students’ reading ability of 2021/2022 ninth year students of SMP swasta Karya Bakti Selesai. Key Words : English Song, TikTok, Reading Ability